(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The Internet of Things (IoT) has evolved from a mere convenience in smart homes to a transformative force that is poised to reshape various industries and sectors. As IoT devices become more integrated into healthcare, transportation, agriculture, and urban planning, the opportunities for increased efficiency, sustainability, and personalization are immense. This paper explores the evolution of IoT, beyond the scope of smart homes, and examines its applications in smart cities, healthcare, agriculture, and the workplace. Additionally, it addresses the security and privacy challenges associated with the widespread deployment of IoT devices. The paper concludes by discussing the future of IoT, focusing on the importance of robust security frameworks to ensure that the full potential of IoT is realized while protecting user data and privacy.